Identifying problems encountered by Thai students in reading classes of English as a Foreign Language - Ivonne Frietche Panjaitan (lppm Universitas Negeri Jakarta, 2023)
The purpose of this research were 1). To investigate the scores correlation from the self-assessment with the high lecturer's summative test. 2). To guide also solve the Thai students problem of reading also listening barriers. 3). The effective self-assessment also teacher's feedback as one of their guidance to improve their reading also listening ability. Research samples were taking from some Cambodian, Vietnamese, Myanmar, Laos, Chinese and Thai Students. At this time mainly the research was concentrate with the Thai students at Rajamanggala University of Technology Wangklaikangwon Campus. As we know exactly their language uses their own characters in writing words which are completely different from Roman Alphabets. They also apply different phonological system. This certainly causes problems for Thai students to learn English, particularly in reading aloud and listening comprehension. This research focused in reading classes in Rajamangala University of Technology Rattanakosin, Thailand and aimed at identifying problems in reading aloud encountered by the students and how self- assessment is conducted and feedbacks may be delivered. Data were derived from the students self- assessment of reading in which they were assigned to record their reading aloud. In this line, a phonetic transcription of some key words from the recorded texts were made and used in the self-assessment. Further, this data were compared to that of teacher's summative test. In comparing the data from both measurement, Pearson Product Moment was applied to see the correlation.